Sortir du cercle infernal traumatique par la fabulation : l’exemple du génocide rwandais dans Le Cavalier et son ombre de Boubacar Boris Diop - Emeline Baudet (Itinéraires)
This paper examines the conditions of dissemination and reception of narratives in the novel Le Cavalier et son ombre, which plunges us into the destiny of a young woman, Khadidja, traumatised by an event comparable to the Rwandan genocide. In contrast to a racist interpretation that would make this event the umpteenth occurrence of a series of collective traumas that are bound to recur in African history, I suggest a reading that highlights the mechanisms of subversion of discourses by leaders and, consequently, the attempts made by the characters to free themselves from them. In order to unravel this mystery and trace the source of this strange and invisible original trauma, the article begins by distinguishing the narrative strata and showing that their intertwining is already a traumatic fabrication. It then explores how the subversion of narrative frameworks unfolds at different levels and exacerbates the characters' traumas, which are buried in attitudes and behaviours that can be described as “madness”. Finally, the article shows that the origin of madness lies less in the genocide itself than in the subversion of discourses – in particular of the narrative scenography of storytelling.